Indications, Hospital Course, and Complexity of Patients Undergoing Tracheostomy at a Tertiary Care Pediatric Hospital. (30th April 2014) - Liu, Charles; Heffernan, Colleen; Saluja, Saurabh; Yuan, Jennifer; Paine, Melody; Oyemwense, Naomi; Berry, Jay; Roberson, David
Abstract : Objective: The purpose of this study was to review inpatients undergoing tracheostomies at a tertiary care pediatric hospital in a 24‐month period and to identify the indications, comorbidities, hospital course, patient complexity, and predischarge planning for tracheostomy care. The goal was to analyze these factors to highlight potential areas for improvement. Study Design: Case series with chart review. Setting: Tertiary care pediatric hospital. Subjects: Ninety‐five inpatients at Boston Children's Hospital requiring a primary or revision tracheostomy during the 24‐month period encompassing 2010 to 2011. Methods: Inpatients undergoing tracheostomy during the study period were identified using 2 different databases: the Boston Children's Hospital Department of Otolaryngology and Communication Enhancement database and institution‐specific information from the Child Health Corporation of America's Pediatric Health Information System (PHIS). We extracted the specified metrics from the inpatient charts. Results: Patients undergoing tracheostomy are complex, with an average of 3.4 comorbidities and 13.6 services involved in their care. The tracheostomy was mentioned in 97.9% of physician and 69.5% of nurse discharge notes, and 42.5% of physician discharge notes contained a plan or appointment for follow‐up. Of the patients, 33.7% were discharged home (27.3% of the nonanatomic group and 52.4% of the anatomic group). Overall, 8.4% of tracheostomy patients died before discharge. Conclusion: The complexity of pediatric tracheostomy patients presents challenges and opportunities for optimizing quality of care for these children. Future directions include the introduction and assessment of multidisciplinary tracheostomy care teams, tracheostomy nurse specialists, and tracheostomy care plans in the pediatric setting.